PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI UNTUK MENINGKATKAN KETERAMPILAN LITERASI AWAL ANAK USIA DINI DI KELOMPOK B TK AL-KHAIRAAT PARIGI KABUPATEN PARIGI MOUTONG - Amrullah, Amrullah; Awalunisah, Sita; Imamah, Zakiyyatul (Jurnal Golden Age, 2025)
This research aims to examine broadly and in depth the development of technology-based learning programs to improve early childhood literacy. In this context, technology-based learning media includes learning through videos specifically designed to improve early childhood literacy skills. With this research, it is hoped that it can provide a deeper understanding of the potential of technology-based learning media in improving early childhood literacy skills, so researchers are interested in conducting research with the title "development of technology-based learning media to improve early childhood literacy in Group B Al-Khairaat Parigi Kindergarten, Parigi Moutong Regency.” This type of research is R&D using the Borg & Gall development model. The data collection techniques for this research are observation, interviews and documentation. The results of this research are that there is effectiveness in developing technology-based learning media to increase the initial literacy of young children in Group B of Al-Khairaat Parigi Kindergarten, Parigi Moutong Regency. This is shown from the data on early childhood literacy which has Sig < α (0.016 < 0.05), which means that early childhood literacy before implementing technology-based learning media is significantly different from after implementing technology-based learning media in Group B Al-Khairaat Parigi Kindergarten, Parigi Moutong Regency. Keywords: technology-based learning media, early childhood literacy